Registration of 'AN38' Facultative Forage Triticale. Issue 3 (1st August 2014) - Lozano-del Río, A. J.; Lozano-Cavazos, C. J.; Ibarra-Jiménez, L.; de la Cruz-Lázaro, E.; Ammar, K.; Mergoum, M.; Pfeiffer, W. H.; Zamora-Villa, V. M.; Colín-Rico, M.; García-Martínez, J. E.; Lozano-Cavazos, E. A.; Gordillo-Melgoza, F. A.; et al.
Abstract : 'AN38' (Reg. No. 2461‐TCL‐015‐010313, Mexico; Reg. No. CV‐33, PI 669387) facultative triticale (× Triticosecale Wittmack) was developed from a cross made by the International Maize and Wheat Improvement Center (CIMMYT), Mexico, and reselected and released as a forage cultivar in Mexico by the Universidad Autónoma Agraria Antonio Narro (UAAAN) and the National Seed Inspection and Certification Service (SNICS) in 2012. AN38 was selected from the progeny of the cross LT1071.82//VICUÑA 4, made in Toluca, Mexico, in 1992. AN38 was released because of its biomass production, earliness, nutritive value, and disease resistance. The selection was based on agronomic, forage, and nutritional characteristics and resistance to stem rust (caused by Puccinia graminis Pers. f. sp. tritici Eriks. & Henn) and leaf rust (caused by P. recondita Rob. ex Desm. f. sp. tritici ). 'TCLF‐AN‐105' facultative triticale (PI 658496), released as a forage cultivar by the UAAAN in 2004 (Reg. No. TCL‐009‐251104, Mexico) was used as reference cultivar.